A new analytical formulation for the stiffness and resistance of the additional plate in bending in beam-to-beam steel joints. (1st February 2021) - Lopez, Manuel; Loureiro, Alfonso; Gutierrez, Ruth; Reinosa, Jose M.
Graphical abstract: Highlights: Study of beam-to-beam bolted steel joints attached by an additional plate. Execution of experimental tests to validate a finite element model. Development of a parametric study with finite element models. Development of an analytical formulation based in an equivalent frame. Presentation of analytical expressions for stiffness and resistance. Abstract: This paper focuses on the stiffness and resistance of the additional plate in bending. This is a component which appears in beam-to-beam bolted steel joints, when a secondary beam with a flush end plate is attached orthogonally to the primary beam by an additional plate welded between its flanges. In this work, six experimental tests have been carried out to calibrate a finite element model which has been used to develop a wide parametric study. Thus, a new formulation for stiffness and resistance based on an equivalent frame is proposed.